Unified model for assessing checkpointing protocols at extreme‐scale. (4th November 2013) - Bosilca, George; Bouteiller, Aurélien; Brunet, Elisabeth; Cappello, Franck; Dongarra, Jack; Guermouche, Amina; Herault, Thomas; Robert, Yves; Vivien, Frédéric; Zaidouni, Dounia
SUMMARY In this paper, we present a unified model for several well‐known checkpoint/restart protocols. The proposed model is generic enough to encompass both extremes of the checkpoint/restart space, from coordinated approaches to a variety of uncoordinated checkpoint strategies (with message logging). We identify a set of crucial parameters, instantiate them, and compare the expected efficiency of the fault tolerant protocols, for a given application/platform pair. We then propose a detailed analysis of several scenarios, including some of the most powerful currently available high performance computing platforms, as well as anticipated Exascale designs. The results of this analytical comparison are corroborated by a comprehensive set of simulations. Altogether, they outline comparative behaviors of checkpoint strategies at very large scale, thereby providing insight that is hardly accessible to direct experimentation. Copyright © 2013 John Wiley & Sons, Ltd.